White Ecclesiology: The Identity of the Church in the Statements on Racism by United States Catholic Bishops - Flipper, Joseph J. (Theological studies, 2021)
The latest United States Conference of Catholic Bishops’ document on racism, Open Wide Our Hearts, prompted numerous criticisms. This article argues that US Catholic bishops’ statements on racism from 1958 to 2018 all too often present an image of the church in which Black, Latinx, Asian, and American Indian identities are spatially and socially the exterior, thereby constructing a white ecclesiology.